Patterns of Creative Tourism Programs for Sam Phan Bok, Pho Sai District, Ubon Ratchathani Province - Pitukpornpunlop, Supattra; Somnuek, Pariwat; Seehanam, Nawathiwa (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This study aimed to 1) analyze former tourism activities in the community, 2) an establishment of creative tourism activities, and 3) suggest forms of creative activities in Sam Phan Bok. The research and Development (R&D) methodology was applied in this study with a total of 30 representatives, comprising 20 tourism entrepreneurs in the area and 10 sample visitors, chosen by purposive Sampling. Content Analysis along with pictures and comparative data tables were employed for data analysis. The findings found in the study were indicated as follows: 1) According to the former activities, sailing for sightseeing along Sam Phan Bok was found and the visitors could learn and exchange their experiences with villagers. The tourists also learn about local lifestyles including the historical backgrounds of the tourist destination; nevertheless, this activity had established in a limited area with hot weather and insufficient facilities for serving visitors. Another form of the activity was a sightseeing walk around Sam Pan Bok. The visitors could see charming stones, gorgeous ponds surrounding the region, and the attractive current of the river Khong passing through the ponds. However, the area for sightseeing was large and the weather was quite hot while lacking facilities to meet visitors’ needs. 2) For the establishment of creative tourism activities, there should be a practical training concerning creative tourism and a sample tour arranged for volunteer visitors such as sailing to see the local lifestyles of fishermen along the river, decorations of hand-held fans made from local bamboo, Ta-Ko making (an authentic Thai dessert made from creamy coconut tapioca and corn pudding) by employing folk wisdom. 3) It is suggested that there are two creative activities in the selected region consisting of a package tour 2 days 1 night and one day trip.